Ultrasound-guided endoscopy to improve accuracy of persistent urogenital sinus (PUGS) diagnosis in adult patient: A case report - Mirandola, Mariateresa; Gui, Benedetta; Naldini, Angelica; Foschi, Nazario; Casula, Viola; Testa, Antonia Carla; Scambia, Giovanni; Catena, Ursula (Frontiers in Surgery, 2023)
Introduction persistent urogenital sinus (PUGS) is a rare condition characterized by abnormal communication between the urethra and vagina, that can frequently be associated with other complex Mullerian malformation (33%). We present a case of PUGS associated with a complex Mullerian malformation diagnosed in adult age after the integration of gynecological ultrasound with hysteroscopy, both performed by expert operators. Case description 27-year-old women was referred to our clinic because of frequent urinary tract infections and cyclic pelvic pain. She was virgo, with normal menstrual cycles and dysmenorrhea. A didelphys uterus and double vagina with bilateral hematocolpos was firstly diagnosed through transrectal and transabdominal ultrasound. An MRI was then performed and a monorenal and ipsilateral ureteral malformation were diagnosed; in addition, a complete absence of the lower third of the vagina and an abnormal origin of the urethra from the bladder were described. Patient underwent lower genital tract endoscopy: external vaginal orifice was obliterated, a PUGS was diagnosed and both vaginas' ostia were detected on the PUGS's posterior-lateral walls. The procedure was performed under transabdominal ultrasound guidance which confirmed the endoscopic anatomical suspicion, avoiding complications such as perforation and misdiagnosis. Discussion ultrasound guided endoscopy plays an essential role in the evaluation of complex anatomic anomalies, such as persistent urogenital sinus (PUGS), leading to a dynamic one-stop diagnosis; it avoids delays and misdiagnosis in preoperative assessment possibly related to the separately application of different radiological and endoscopic techniques.